Knowledge and Surroundings: Notes for an epistemology of territory (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Territory is a reality which manifests itself through a plurality of areas and factions that we will call here perspectives. Two of them seem to us,  theoretically, are always correlative: the metaphysical perspective and the epistemological perspective. According to the first, territory is a kind of effective reality, though not always in a concrete fashion, while the second is a notional reality, a concept, a theory. In this essay we approach territory through this second condition, reviewing what we generally understand asepistemic reality; and what territory seems to be to us in regard to an epistemic reality, and we indicate the correlations that appear between both perspectives.
Keywords: Space; territory; spaciality; territoriality